Pre-operative intraocular pressure as a predictor of post-operative intraocular pressure after phacoemulsification in non-glaucomatous patients - Ernawati, Titiek; Hendrawan, Kevin Anggakusuma; Khudrati, Wilson Christianto; Samsudin, Kevin (Faculty of Medicine, Universitas Trisakti, 2022)
BackgroundCataract has been known to cause high intraocular pressure which may lead to secondary glaucoma. Some anatomical changes in cataract patients are assumed to be factors contributing to increased intraocular pressure (IOP). The changes in IOP after cataract surgery tend to help surgeons to predict clinical outcomes. Therefore, IOP control is very important in these patients. This study aimed to determine the ocular biometric parameters and pressure-to-depth (PD) ratio associated with IOP in non-glaucomatous patients who undergo cataract surgery. MethodsA prospective study using secondary clinical data collected from 81 non-glaucomatous patients. Data were collected by examining each subject pre- and post-operatively. The changes in ocular biometry parameters and IOP were measured one week before surgery and 8 weeks after the surgery. Univariate and multivariate linear regression were performed to analyze the data. ResultsThe mean anterior chamber depth (ACD) change was 0.73 ± 0.16 mm, mean PD ratio was 5.04 ± 1.16, and the mean pre-operative IOP was 16.07 ± 2.92 mmHg, decreasing by 2.35 mm Hg (14.6 %) to 13.72 ± 3.42 mm Hg at 8 weeks postoperatively. Univariate linear regression results showed a significant correlation between PD ratio and post-operative IOP (p=0.000), but no significant association was observed between PD ratio and post-operative IOP in multiple linear regression (p=0.126). However, pre-operative IOP was significantly associated with post-operative IOP (Beta=1.244; p=0.004) ConclusionsOur data demonstrated that pre-operative IOP was the most influential risk factor of IOP reduction after phacoemulsification in non-glaucomatous patients.